Potential Health Risks Associated to ICSI: Insights from Animal Models and Strategies for a Safe Procedure - Sánchez-Calabuig, María Jesús; López-Cardona, Angela Patricia; Fernández-González, Raúl; Ramos-Ibeas, Priscila; Fonseca Balvís, Noelia; Laguna-Barraza, Ricardo; Pericuesta, Eva; Gutiérrez-Adán, Alfonso; Bermejo-Álvarez, Pablo (Frontiers in Public Health, 2014)
Artificial reproductive techniques are currently responsible for 1.7–4% of the births in developed countries and intracytoplasmatic sperm injection (ICSI) is the most commonly used, accounting for 70–80% of the cycles performed. Despite being an invaluable tool for infertile couples, the technique bypasses several biological barriers that naturally select the gametes to achieve an optimal embryonic and fetal development. In this perspective, ICSI has been associated with an increased risk for diverse health problems, ranging from premature births and diverse metabolic disorders in the offspring to more severe complications such as abortions, congenital malformations, and imprinting disorders. In this review, we discuss the possible implications of the technique per se on these adverse outcomes and highlight the importance of several experiments using mammalian models to truthfully test these implications and to uncover the molecular base that origins these health problems. We also dissect the specific hazards associated to ICSI and describe some strategies that have been developed to mimic the gamete selection occurring in natural conception in order to improve the safety of the procedure.